2019
DOI: 10.3390/rs11242952
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Phenotyping of Indirect Traits for Early-Stage Selection in Sugarcane Breeding

Abstract: One of the major limitations for sugarcane genetic improvement is the low heritability of yield in the early stages of breeding, mainly due to confounding inter-plot competition effects. In this study, we investigate an indirect selection index (Si), developed based on traits correlated to yield (indirect traits) that were measured using an unmanned aerial vehicle (UAV), to improve clonal assessment in early stages of sugarcane breeding. A single-row early-stage clonal assessment trial, involving 2134 progenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…Kaler et al 14 reported a broad sense heritability (H) of 19% for CT in a diverse panel of soybean accessions evaluated in different environments using GWAS. Likewise, low to moderate broad sense heritability of CT/CTD was reported in wheat (H = 16% to 38%) 79 81 , in sugarcane (H = 9% to 44%) 82 , and in rice (H = 21% to 30%) 83 . The low heritability of CT/CTD in soybean and other crops indicate that this trait is highly influenced by environmental conditions 84 .…”
Section: Discussionmentioning
confidence: 96%
“…Kaler et al 14 reported a broad sense heritability (H) of 19% for CT in a diverse panel of soybean accessions evaluated in different environments using GWAS. Likewise, low to moderate broad sense heritability of CT/CTD was reported in wheat (H = 16% to 38%) 79 81 , in sugarcane (H = 9% to 44%) 82 , and in rice (H = 21% to 30%) 83 . The low heritability of CT/CTD in soybean and other crops indicate that this trait is highly influenced by environmental conditions 84 .…”
Section: Discussionmentioning
confidence: 96%
“…Measuring gas exchange at different levels of the canopy is complicated by the decoupling effects between leaf and the atmosphere, wherein it has been shown that the leaves at the base of a canopy are potentially more decoupled from the atmosphere than top canopy leaves (Jarvis and McNaughton, 1986). The rapidly advancing aerial field phenomics technologies currently being evaluated in sugarcane breeding (Natarajan et al ., 2019) may offer solutions for the practical application of i TE for variety development.…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly advancing aerial field phenomics technologies currently being evaluated in sugarcane breeding (Natarajan et al, 2019) may offer solutions for the practical application of i TE for variety development.…”
Section: Genetic Correlation Between I Te and Cane Yield Maximised Under Certain G S Rangesmentioning
confidence: 99%
“…Moreover, family selection can be improved by techniques such as high‐throughput phenotyping and genome selection. In the first situation, phenotyping is time consuming and an expensive procedure (Natarajan et al., 2019; Costa et al., 2019). The use of remote‐sensing technique based on unmanned aerial vehicle (UAV) is promising, especially, for the possibility of finding new variables to integrate in the sugarcane breeding pipeline.…”
Section: Discussionmentioning
confidence: 99%